Distribution of chloramphenicol to tissues, plasma and urine in pigs after oral intake of low doses. Issue 9 (1st September 2016) - Aspenström-Fagerlund, Bitte; Nordkvist, Erik; Törnkvist, Anna; Wallgren, Per; Hoogenboom, Ron; Berendsen, Bjorn; Granelli, Kristina
ABSTRACT: Toxic effects of chloramphenicol in humans caused the ban for its use in food-producing animals in the EU. A minimum required performance level (MRPL) was specified for chloramphenicol at 0.3 μg kg –1 for various matrices, including urine. In 2012, residues of chloramphenicol were found in pig urine and muscle without signs of illegal use. Regarding its natural occurrence in straw, it was hypothesised that this might be the source, straw being compulsory for use as bedding material for pigs in Sweden. Therefore, we investigated if low daily doses of chloramphenicol (4, 40 and 400 μg/pig) given orally during 14 days could result in residues in pig tissues and urine. A dose-related increase of residues was found in muscle, plasma, kidney and urine (showing the highest levels), but no chloramphenicol was found in the liver. At the lowest dose, residues were below the MRPL in all tissues except in the urine. However, in the middle dose, residues were above the MRPL in all tissues except muscle, and at the highest dose in all matrices. This study proves that exposure of pigs to chloramphenicol in doses occurring naturally in straw could result in residues above the MRPL in plasma, kidney and especially urine.